2021
DOI: 10.1101/2021.11.01.465941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polyamines and eIF5A hypusination facilitate SREBP2 translation and cholesterol synthesis to enhance enterovirus attachment and infection

Abstract: Metabolism is key to cellular processes that underlie the ability of a virus to productively infect. Polyamines are small metabolites vital for many host cell processes including proliferation, transcription, and translation. Polyamine depletion also inhibits virus infection via diverse mechanisms, including inhibiting polymerase activity and viral translation. We showed that Coxsackievirus B3 (CVB3) attachment requires polyamines; however, the mechanism was unknown. Here, we report polyamines’ involvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The connection between polyamines and cholesterol synthesis has important implications for the effects of connected metabolic pathways on virus infection. Prior work showed that serum sterol levels were reduced in rats and mice treated with DFMO. , Our work, both here and in a previous one, demonstrates that polyamines support cholesterol synthesis through translation of SREBP2, a critical transcription factor for cholesterol biosynthetic genes. We previously showed that Coxsackievirus B3 attachment relied on both polyamines and the connected cholesterol synthetic pathway for infection.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The connection between polyamines and cholesterol synthesis has important implications for the effects of connected metabolic pathways on virus infection. Prior work showed that serum sterol levels were reduced in rats and mice treated with DFMO. , Our work, both here and in a previous one, demonstrates that polyamines support cholesterol synthesis through translation of SREBP2, a critical transcription factor for cholesterol biosynthetic genes. We previously showed that Coxsackievirus B3 attachment relied on both polyamines and the connected cholesterol synthetic pathway for infection.…”
Section: Discussionsupporting
confidence: 77%
“…We recently demonstrated that cellular polyamines promote cholesterol synthesis through polyamine-mediated SREBP2 translation and activity . We thus hypothesized that polyamine depletion via DFMO and subsequent cholesterol depletion would result in reduced RVFV replication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyamines are critical molecules for both cellular functions ( 17 ) and CVB3 replication ( 14 , 18 , 19 ), and we hypothesized that persistent replication might be due to changes in polyamine metabolism, resulting in a detente between the virus and the host. Our observation of the emergence of mutant CVB3 (VP3 Q234R ), resistant to polyamine depletion, further highlighted this potential connection.…”
Section: Resultsmentioning
confidence: 99%